The link between turbulence, magnetic fields, filaments, and star formation in the central molecular zone cloud G0.253+0.016 - Federrath, Christoph; Kruijssen, Diederik (The astrophysical journal, 2016)
Star formation is primarily controlled by the interplay between gravity, turbulence, and magnetic fields. However, the turbulence and magnetic fields in molecular clouds near the Galactic center may differ substantially compared to spiral-arm clouds. Here we determine the physical parameters of the central molecular zone (CMZ) cloud G0.253+0.016, its turbulence, magnetic field, and filamentary structure. Using column density maps based on dust-continuum emission observations with ALMA+ Herschel , we identify filaments and show that at least one dense core is located along them. We measure the filament width ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn1.gif] $W_\mathrmfil=0.17± 0.08\,\mathrmpc$ and the sonic scale ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn2.gif] $λ _\mathrmsonic=0.15± 0.11\,\mathrmpc$ of the turbulence, and find ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn3.gif] $W_\mathrmfil≈ λ _\mathrmsonic$ . A strong velocity gradient is seen in the HNCO intensity-weighted velocity maps obtained with ALMA+Mopra. The gradient is likely caused by large-scale shearing of G0.253+0.016, producing a wide double-peaked velocity probability distribution function (PDF). After subtracting the gradient to isolate the turbulent motions, we find a nearly Gaussian velocity PDF typical for turbulence. We measure the total and turbulent velocity dispersion, ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn4.gif] $8.8± 0.2\,\mathrmkm\,\rms^-1$ and ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn5.gif] $3.9± 0.1\,\mathrmkm\,\rms^-1$ , respectively. Using magnetohydrodynamical turbulence simulations, we find that G0.253+0.016's turbulent magnetic field ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn6.gif] $B_\mathrmturb=130± 50\,μ \rmG$ is only ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn7.gif] $\lesssim 1/10$ of the ordered field component. Combining these measurements, we reconstruct the dominant turbulence driving mode in G0.253+0.016 and find a driving parameter of ##IMG## [http://ej.iop.org/images/0004-637X/832/2/143/apjaa4151ieqn8.gif]